Commercial fishing, Inuit rights, and internal colonialism in Nunavut. (6th January 2022) - Bernauer, Warren
Abstract: This paper considers the degree to which the concept of 'internal colonialism' accurately describes the political economy of Nunavut's commercial fisheries. Offshore fisheries adjacent to Nunavut were initially dominated by institutions based in southern Canada, and most economic benefits were captured by southern jurisdictions. Decades of political struggle have resulted in Nunavut establishing a role for itself in both the management of offshore resources and the operation of the offshore fishing industry. However, key decisions about fishery management are made by the federal government, and many benefits from Nunavut's offshore fisheries continue to accrue to southern jurisdictions. The concept of internal colonialism is therefore a useful concept for understanding the historical development and contemporary conflicts over offshore fisheries. By contrast, Nunavut's inshore fisheries were established as community development initiatives intended to promote economic well-being and stability. While inshore fisheries primarily benefit Inuit community economies, the growth of inshore fisheries has been hampered by small profit margins, inadequate marine infrastructure, and a dearth of baseline data. The federal government's failure to support the expansion of inshore fisheries is a manifestation of internal colonialism, insofar as it reflects an unequal distribution of public infrastructure and research.